Evaluation of Yield, Reaction to Diseases, and Grain Physical Attributes of Some Introduced Rice Hybrids in Ghana. (13th March 2019) - Abebrese, Samuel Oppong; Yeboah, Alex; Dogbe, Wilson; Dartey, Paul Kofi Ayirebi; Akromah, Richard; Gracen, Vernon Edward; Offei, Samuel Kwame; Danquah, Eric Yirenkyi
Abstract : Hybrid rice technology is one of the promising, sustainable, and proven technologies for increasing rice production and productivity with a yield advantage of 15–30% over modern inbred varieties. The potential of hybrid rice has so far not been exploited in Ghana. This study was undertaken to evaluate the yield potential, reaction to diseases, and physical grain attributes of some introduced hybrids. The trials were laid out in a randomized complete block design (RCBD) with three replicates across three locations. Data were taken on grain yield, yield components, reaction to diseases, and grain physical characteristics. Four promising hybrids (SWARNA 2, ARGH 1501, ARGH 1502, and ARGH 1503) with a mean yield advantage of 15–20.8% over the best inbred check "AgraRice" were identified. With few exceptions, the hybrids were broadly adapted and had adequate resistance to blast and bacterial leaf blight. Most of the test hybrids had long slender grains which make them acceptable to the Ghanaian market but lacked aroma.